ANALISIS FAKTOR-FAKTOR INTRINSIK YANG BERHUBUNGAN DENGAN KEJADIAN PNEUMONIA PADA BALITA DI PUSKESMAS I DENPASAR SELATAN - Melynia, Ni Putu; Parwati, Ni Wayan Manik; Indriana, Ni Putu Riza Kurnia (STIKES ADVAITA MEDIKA TABANAN, 2024)
Background: One disease that is prone to attack toddlers is pneumonia. Pneumonia is the world’s leading killer of children under five compared to other diseases such as AIDS, malaria and measles combined. The purpose of this study was to identify the analysis of intrinsic factors associated with pneumonia in toddlers at Public Health Center I South Denpasar Method: This study employed a correlational research design with a population of 128 toddlers. Moreover, 67 respondents were recruited purposively as the sample. The data were collected through questionnaires and google forms. Results: Findings indicated no correlation between age (p=0,158), gender (p=0,895), nutritional status (p=0,122), history of low birth weight babies (p=0,321), and administration of vitamin A (p=0,770) with the occurrence of pneumonia in toddlers with a p value > 0.05. Moreover, there was a correlation between immunization status (p=0,000), history of exclusive breastfeeding (p=0,000) and pneumonia occurrences in toddlers with a p-value < 0.05. Conclusion: From this study, two intrinsic factors are associated with pneumonia in toddlers: immunization status and history of exclusive breastfeeding. Keywords: Toddler Pneumonia, characteristics